Outrunning free radicals in room-temperature macromolecular crystallography. - Owen, R; Axford, D; Nettleship, J; Owens, R; Robinson, J; Morgan, A; Doré, A; Lebon, G; Tate, C; Fry, E; Ren, J; Stuart, D; et al. (2012)
A significant increase in the lifetime of room-temperature macromolecular crystals is reported through the use of a high-brilliance X-ray beam, reduced exposure times and a fast-readout detector. This is attributed to the ability to collect diffraction data before hydroxyl radicals can propagate through the crystal, fatally disrupting the lattice. Hydroxyl radicals are shown to be trapped in amorphous solutions at 100 K. The trend in crystal lifetime was observed in crystals of a soluble protein (immunoglobulin γ Fc receptor IIIa), a virus (bovine enterovirus serotype 2) and a membrane protein (human A(2A) adenosine G-protein coupled receptor). The observation of a similar effect in all three systems provides clear evidence for a common optimal strategy for room-temperature data collection and will inform the design of future synchrotron beamlines and detectors for macromolecular crystallography.